Zhuang Song Preservation Efforts - Jähnichen, Gisa; Zhi, Lin (Cultural Arts Research and Development, 2023)
Songs are at the centre of music transmission in many educational institutions around the world. People in China say ‘song’, but they may mean “music and dance” or they just mean all consciously produced sounds they are confronted with in their daily lives, such as rap coming out of a technical device or the noise of birds around a trash bin. One of the main ways to overcome these shortcomings is to break up with conventional habits of holding on to assumptive statements without having clarified their purpose and diversification from sources taken as ‘the original ones’. Millions of songbooks and text collections are published and distributed. They are offering easy teaching and easy performing on stages in front of an unknown majority. Using songs and other ‘easy-to-teach’-items for presenting research goals could lead to many misunderstandings in more complex situations of cultural life, which absorb over time many different appearances of sound, a large part of which is commercial output. This cannot be ignored and should inspire further discussions.